Navigating the Career Transition from Industry to Academia. (February 2014) - Wilson, Michael John; Wood, Leigh; Solomonides, Ian; Dixon, Peter; Goos, Merrilyn
Transitions from 'industry' to 'academia' represent a unique type of career change. Although such transitions are becoming increasingly common in Australian universities and beyond, there is no coherent framework for making sense of the multiple and intersecting factors involved in these inter-domain movements. This form of occupational transition challenges the traditional and increasingly outdated conception of the linear academic tenure track. Thus, in order to revise the notion of the tenure track and gain a fuller understanding of these career trajectories, we must seek to understand the motivations for such occupational movements as well as the short-term, medium-term and long-term social, emotional and professional needs and preferences of practitioner-academics having made this transition. This article presents an attempt to re-think the imagery and language that have come to characterize this type of career movement as well as the attitudes within and between industry and academia. The authors advocate that transitions from industry to academia do not require the dismantling of linkages between the two fields, but rather are made more meaningful and effective when pre-existing professional and personal linkages are maintained and encouraged.